What if I'm wrong? : and other key questions for decisive school leadership - Rodberg, Simon (ASCD, 2020)
"Simon Rodberg's five-question framework uses the latest research in cognitive science to help principals navigate tough dilemmas and everyday challenges to become decisive school leaders"--